2021
DOI: 10.21037/atm-20-5541
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of free triiodothyronine and N-terminal pro-B-type natriuretic peptide for patients with acute myocardial infarction undergoing percutaneous coronary intervention: a prospective cohort study

Abstract: Background: Altered thyroid function and increased N-terminal pro-B-type natriuretic peptide (NT-proBNP) are prognostic factors in acute myocardial infarction (AMI). The study aims to investigate whether free triiodothyronine (fT3) and NT-proBNP are prognostic factors for long-term outcomes in patients with AMI undergoing percutaneous coronary intervention (PCI).Methods: This was an observational, prospective, single-center study of consecutive patients enrolled at Fuwai Hospital between January, 2013 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Patients with AMI tend to have low level of FT3, and severe cases even have low T3 syndrome [15]. A meta-analysis showed that low T3 syndrome is an independent risk factor for poor prognosis of cardiovascular diseases and associated with increased risks of all-cause death, cardiovascular death, and major adverse cardiovascular events (MACE) [ [19]. This study mainly observed the relationship between the FT3 level and the onset of long-term HF in AMI patients treated with and without PCI, and we found that low FT3 level was an independent risk factor for long-term HF in AMI patients and had a predictive value for the occurrence of long-term HF after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AMI tend to have low level of FT3, and severe cases even have low T3 syndrome [15]. A meta-analysis showed that low T3 syndrome is an independent risk factor for poor prognosis of cardiovascular diseases and associated with increased risks of all-cause death, cardiovascular death, and major adverse cardiovascular events (MACE) [ [19]. This study mainly observed the relationship between the FT3 level and the onset of long-term HF in AMI patients treated with and without PCI, and we found that low FT3 level was an independent risk factor for long-term HF in AMI patients and had a predictive value for the occurrence of long-term HF after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to these diverse scoring systems, a singular, rapid, and objective index holds advantages for disease severity assessment and prognosis. Abundant research underscores the association of free thyroid hormone T3 (FT3) with the prognosis of various conditions, including sepsis, heart failure, myocardial infarction, COVID-19, cardiomyopathy, liver failure associated with hepatitis B virus, and pulmonary arterial hypertension (5)(6)(7)(8)(9)(10)(11). FT3 has emerged as an independent prognostic indicator for ICU patients.…”
Section: Introductionmentioning
confidence: 99%